한식점의 경영성과에 영향을 미치는 요인 분석 - 강혜정 (한국농촌경제연구원, 2013)
This study is designed to analyze the determinants of management performance of Korean food restaurants, using a national survey data. The ordered logit model and the quantile regression method are applied to analyze the factors affecting the business status and the sales per employee, respectively. The results demonstrate that operator’s human capital such as educational background and participation of training programs contributes to the advancement of management performance. Also, economies of scale plays important roles in improving management performance of Korean food restaurants.